Exploring Self-Identity in Are You There God? It’s Me, Margaret: A Psychosocial Perspective - Salsabila, Rizky Shufiya; Nugroho, Abdillah (JELITA, 2025)
The research analyzes the process of identity formation in adolescence experienced by Margaret, the main character in the film Are You There God? Its Me, Margaret and relates it to concepts in identity theory, particularly Erik Erikson's psychosocial theory. This research uses descriptive-qualitative methods and literature studies by focusing on literature in the form of film scripts. The research object includes the movie script and focuses on Margaret's search for self-identity. Data was collected through literature research, using primary data from the movie and secondary data from articles, author biographies, and books related to the research. This data collection method is in accordance with the problem formulation and research objectives. The data analysis stage uses content analysis, including identification, classification, and interpretation of Margaret's character in the movie. The results show that there are four points of results during Margaret's search for self-identity, namely aspects of confusion over self-identity, beliefs that are adopted, search through internal dialogue with God, and conformity with Erik Erikso's theory of self-identity. From all the conflicts experienced by Margaret, she was able to get through the stage by finding confidence, having a clear direction, and even being able to remain herself.